Quantitative Determination of Ascorbic Acid in Herbal Medicinal Products by HPLC - T. A. Golomazova; E. P. Shefer; S. S. Prokhvatilova; N. P. Antonova (Регуляторные исследования и экспертиза лекарственных средств, 2023)
Ascorbic acid (vitamin C) is involved in many vital biochemical processes in the human body. Rose hips are a natural source of ascorbic acid. Rose hips are used in decoctions and many vitamin herbal teas. Russian compendial methods for the quantitative determination of ascorbic acid have certain limitations precluding its objective measurement in herbal drugs, herbal drug preparations, and herbal medicinal products.The aim of the study was to develop an analytical procedure for the quantitative determination of ascorbic acid in herbal drugs, herbal medicinal preparations, and herbal medicinal products using high performance liquid chromatography (HPLC).Materials and methods. The study involved two herbal medicinal products, Rose Hips (rose hips) and Vitamin Herbal Tea 2 (rose hips and rowan fruits), and reference standards for ascorbic acid, rutoside, quercetin, gallic acid, caffeic acid, chlorogenic acid, luteolin-7-glucoside, citric acid, DL-malic acid, thiamine, and pyridoxine hydrochloride. The authors used a 1260 Infinity II chromatograph with a diode array detector by Agilent and an Inertsil ODS-3 chromatographic column (250 mm × 4.6 mm, 5 µm) by GL Sciences. The HPLC system was operated in gradient elution mode, and the detector was set at 244 nm.Results. Ascorbic acid content in herbal drugs, herbal medicinal preparations, and herbal medicinal products can be determined by HPLC. Adequate sample preparation and chromatography conditions allow for inhibiting ascorbic acid oxidation in aqueous solutions for a period sufficient to complete testing (not less than 8 h).Conclusions. The authors developed a highly sensitive and selective HPLC procedure for the quantitative determination of ascorbic acid intended for the standardisation of herbal drugs, herbal medicinal preparations, and herbal medicinal products. The procedure is worthy of inclusion in the Rose Hips and Vitamin Herbal Tea 2 monographs of the State Pharmacopoeia of the Russian Federation. Switching to HPLC should not require lowering the limit for ascorbic acid (not less than 0.2%) established in the Rose Hips and Vitamin Herbal Tea 2 monographs for the titration method. The ascorbic acid content was below this limit in the vast majority of study samples. However, this discrepancy may be explained by the presence of dog rose (Rosa canina) species low in vitamin C, which should normally be used only as choleretics.